2006
DOI: 10.1200/jco.2006.06.3701
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tumor-Specific Molecular Signatures in Intracranial Ependymoma and Association With Clinical Characteristics

Abstract: The present exploratory molecular profiling study allowed us to refine previously reported intervals of genomic imbalance, to identify novel restricted regions of gain and loss, and to identify molecular signatures correlating with various clinical variables. Validation of these results on independent data sets represents the next step before translation into the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
162
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(187 citation statements)
references
References 33 publications
15
162
0
9
Order By: Relevance
“…Despite this, similar findings were shown by one aCGH study of 24 intracranial ependymomas that revealed that tumors from younger patients had significantly smaller, partial regions of genomic imbalances than older patients (76).…”
Section: Molecular Distinctions Between Pediatric and Adult Ependymomasmentioning
confidence: 69%
See 2 more Smart Citations
“…Despite this, similar findings were shown by one aCGH study of 24 intracranial ependymomas that revealed that tumors from younger patients had significantly smaller, partial regions of genomic imbalances than older patients (76).…”
Section: Molecular Distinctions Between Pediatric and Adult Ependymomasmentioning
confidence: 69%
“…The region 22q13.3 has also been highlighted as a frequent region of genomic loss in ependymoma (76,156,157). Gene expression analysis within this locus has revealed downregulation of SULT4A, a gene widely expressed in several compartments of the human brain (76,77,148).…”
Section: Immunohistochemical and Genomic Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, elevated expression of TLX has been reported in various types of human glioma [68][69][70][71][72][73] and glioma cell lines [74], and TLX overexpression seems to be associated with a poor prognosis for patients with glioma [74]. A recent study further reported that TLX promotes the progression of neuroblastoma and is correlated with poor survival [56].…”
Section: Tlx and Human Diseasesmentioning
confidence: 99%
“…60,[62][63][64][65][66][67][68][69][70][71] Beside its genomic amplification, YAP protein levels and nuclear localization have been shown to be elevated in multiple types of cancer. 31,60,[72][73][74][75] Overexpression of YAP in mammary epithelial cells is sufficient to promote epithelial-mesenchymal transition (EMT), induce a proliferative advantage, inhibit apoptosis and induce anchorage-independent growth, characteristics associated with transforming oncogenes. 76 YAP oncogenic activity was also demonstrated in a mouse model of hepatocellular carcinoma, where YAP amplification contributes to tumor development.…”
Section: Sav1 (Ww45)mentioning
confidence: 99%